Bayesian reconstruction of the evolutionary history and cross‐species transition of variola virus and orthopoxviruses. Issue 6 (12th March 2018) - Zehender, Gianguglielmo; Lai, Alessia; Veo, Carla; Bergna, Annalisa; Ciccozzi, Massimo; Galli, Massimo
Abstract : Variola virus (VARV), the causative agent of smallpox, is an exclusively human virus belonging to the genus Orthopoxvirus, which includes many other viral species covering a wide range of mammal hosts, such as vaccinia, cowpox, camelpox, taterapox, ectromelia, and monkeypox virus. The tempo and mode of evolution of Orthopoxviruses were reconstructed using a Bayesian phylodynamic framework by analysing 80 hemagglutinin sequences retrieved from public databases. Bayesian phylogeography was used to estimate their putative ancestral hosts. In order to estimate the substitution rate, the tree including all of the available Orthopoxviruses was calibrated using historical references dating the South American variola minor clade (alastrim) to between the XVI and XIX century. The mean substitution rate determined by the analysis was 6.5 × 10 ‐6 substitutions/site/year. Based on this evolutionary estimate, the time of the most recent common ancestor of the genus Orthopoxvirus was placed at about 10 000 years before the present. Cowpox virus was the species closest to the root of the phylogenetic tree. The root of VARV circulating in the XX century was estimated to be about 700 years ago, corresponding to about 1300 AD. The divergence between West African and South American VARV went back about 500 years ago (falling approximately in the XVI century). A rodent species is the most probable ancestral host from which the ancestors of all the known Orthopoxviruses were transmitted to the other mammal host species, and each of these species represented a dead‐end for each new poxvirus species, without any further inter‐specific spread.